Use of oily extract of Pleuroncodes monodon as pigment in the feed of the rainbow trout (Oncorhynchus mykiss) - Montufar, Paul (2021)
The IM of this study to evaluate the oily extract of the squat lobster Pleuroncodes monodon in the balanced feed on the pigmentation of the muscle of the rainbow trout (Oncorhynchus mykiss). The treatments were T1: feed formulated without pigment, T2 and T3: feed with 70 and 90 mg of natural astaxanthin/kg of feed, respectively, and T4 feed with synthetic pigment (70 mg of astaxanthin/kg of feed). The color values were recorded every 15 days and for 90 days using the Roche SalmoFanR colorimetric rule and the L*, a*, b*, C* and H* values of the dorsal and caudal zone of the trout. The results of the color readings indicated that the treatments T2, T3 and T4 obtained with the SalmoFanR rule did not show significant differences between them; however, the measurement obtained with the colorimeter showed differences in the color of T4 with respect to T2 and T3. It is concluded that the addition of 70 mg of natural astaxanthin per kilogram of feed achieves pigmentation similar to that obtained with synthetic astaxanthin.